Spatial patterns of genome‐wide expression profiles reflect anatomic and fiber connectivity architecture of healthy human brain. Issue 8 (22nd February 2014) - Goel, Pragya; Kuceyeski, Amy; LoCastro, Eve; Raj, Ashish
Abstract Unraveling the relationship between molecular signatures in the brain and their functional, architectonic, and anatomic correlates is an important neuroscientific goal. It is still not well understood whether the diversity demonstrated by histological studies in the human brain is reflected in the spatial patterning of whole brain transcriptional profiles. Using genome‐wide maps of transcriptional distribution of the human brain by the Allen Brain Institute, we test the hypothesis that gene expression profiles are specific to anatomically described brain regions. In this work, we demonstrate that this is indeed the case by showing that gene similarity clusters appear to respect conventional basal‐cortical and caudal‐rostral gradients. To fully investigate the causes of this observed spatial clustering, we test a connectionist hypothesis that states that the spatial patterning of gene expression in the brain is simply reflective of the fiber tract connectivity between brain regions. We find that although gene expression and structural connectivity are not determined by each other, they do influence each other with a high statistical significance. This implies that spatial diversity of gene expressions is a result of mainly location‐specific features but is influenced by neuronal connectivity, such that like cellular species preferentially connects with like cells. Hum Brain Mapp 35:4204–4218, 2014. © 2014 Wiley Periodicals, Inc.